No man is an island: management of the emergency response to the SARS-CoV-2 (COVID-19) outbreak in a large public decentralised service delivery organisation - Mikael Ohrling; Karin Solberg Carlsson; Mats Brommels (BMC, 2022)
Abstract Background We wanted to better understand whether and how agility can be achieved in a decentralised service delivery organisation in Sweden. The pandemic outbreak of SARS-Cov-2 (Covid-19) provided an opportunity to assess decentralisation as a strategy to improve the responsiveness of healthcare and at the same time handle an unpredictable and unexpected event. Methods Data from in-depth interviews with a crisis management team (n = 23) and free text answers in a weekly survey to subordinated clinical directors, i.e. unit managers, (n = 108) were scrutinised in a directed content analysis. Dynamic capabilities as a prerequisite for dynamic effectiveness, understood as reaching strategic and operative effectiveness simultaneously, were explored by using three frameworks for dynamic effectiveness, dynamic capabilities and delegated authority in a decentralised organisation. Results Unpredictable events, such as the pandemic Covid-19 outbreak, demand a high grade of ability to be flexible. We find that a high degree of operational effectiveness, which is imperative in an emergency situation, also is a driver of seeking new strategic positions to even better meet new demands. The characteristics of the dynamic capabilities evolving from this process are described and discussed in relation to decentralisation, defined by decision space, organisational and individual capacity as well as accountability. We present arguments supporting that a decentralised management model can facilitate the agility required in an emergency. Conclusions This study is, to our knowledge, the first of its kind where a decentralised management model in a service delivery organisation in healthcare is studied in relation to crisis management. Although stemming from one organisation, our findings indicating the value of decentralisation in situations of crisis are corroborated by theory, suggesting that they could be relevant in other organisational settings also.